Slang Words Used by the Millennial Indonesian Generation in TikTok - Manihuruk, Leo Lihardo; Ginting, Desinta; Manik, Sondang; Manurung, Lastri W (Journal of Applied Linguistics, 2025)
Language is used in various ways, especially among the younger generation. The millennial generation, in particular, exhibited a higher tendency to use slang in daily conversations rather than formal language. This study aimed to analyze the phenomenon of slang words used by the millennial generation on TikTok. The research investigated the types of slang employed by millennials on TikTok and explored the meanings of these slang words. A descriptive qualitative approach was applied, and data were obtained through observation. The analyzed data consisted of videos and comments collected from TikTok users (@adridilapangasebagaipap and @slametnovendraa) between January 12 and January 19, 2024. The findings revealed that 435 slang words were used during the observed period. These words fell into three types of slang: imitative, acronyms, and clipping. Additionally, four frequently used slang words were identified: "Baper," which conveys emotions and feelings, appeared 150 times; "Sus," meaning suspicious, appeared 120 times; "Lit," referring to energy and happiness, appeared 90 times; and "Vibes," describing mood, appeared 75 times. The study highlighted the prominent role of slang in the communication of the millennial generation on TikTok, reflecting their linguistic creativity and adaptability to digital platforms. Keywords : slang, types of slang, millennial generation